Energy-efficient electrolytic hydrogen generation using a Cu3P nanoarray as a bifunctional catalyst for hydrazine oxidation and water reduction. Issue 3 (3rd February 2017) - Liu, Meng; Zhang, Rong; Zhang, Lixue; Liu, Danni; Hao, Shuai; Du, Gu; Asiri, Abdullah M.; Kong, Rongmei; Sun, Xuping
Abstract : A Cu3 P nanoarray acts as a durable bifunctional catalyst for hydrogen evolution reaction and hydrazine oxidation reaction with 100 mA cm −2 at 0.72 V in 1.0 M KOH. Abstract : Energy-efficient electrolytic hydrogen generation is highly desired but still remains challenging. In this work, we demonstrate that a Cu3 P nanoarray on copper foam (Cu3 P/CF) behaves as a high-performance electrocatalyst for hydrazine oxidation reaction (HzOR) in alkaline electrolytes. A full electrolytic system employing Cu3 P/CF as both an anode for HzOR and a cathode for hydrogen evolution reaction drives 100 mA cm −2 at a voltage of 0.72 V in 1.0 M KOH aqueous solution with 0.5 M hydrazine. It also demonstrates high long-term stability.